PENGEMBANGAN USAHA BUDIDAYA RUMPUT LAUT DI DESA NURUWE KABUPATEN SERAM BAGIAN BARAT - Anwar Tuahuns; St. M. Siahainenia; B. M. Leimeheriwa (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2022)
This study aims to examine the development of seaweed cultivation in Nuruwe Village, West Seram Regency. Primary data were collected through 4 respondents in the cultivation group with direct interviews and direct field observations of the object under study. Data were analyzed using qualitative analysis methods, namely productivity analysis, growth analysis, income analysis and financial ratios (BEP, ROI, R/C) and development strategy through SWOT and AHP analysis. The results showed that seaweed production was classified as productive, the absolute growth of seaweed had increased, seaweed cultivation was feasible to be developed and the development strategy resulted in 6 priority strategies, namely a). First Priority: Establishment of Seaweed Cultivation Institution b). Second Priority: Improving Cultivation Facilities and Infrastructure c). Third Priority: Water Conservation and Law Enforcement d). Fourth Priority: Seaweed Cultivation Technical Training e). Fifth Priority: Enlarging Cultivation Business f). Sixth Priority: Increased Seaweed Production.